“Loved with an L…”: The Lesbian Continuum in Three Works by Sylvia Townsend Warner - Paul, Ronald (Nordic Journal of English Studies, 2014)
This article takes as its critical point of departure Adrienne Rich’s concept of a lesbian continuum of female sisterhood, support and dissent against the norms of patriarchal society. In particular, Rich’s term is used to explore three key works from the 1930s by the English writer, Sylvia Townsend Warner – Opus 7, Whether a Dove or Seagull and Summer Will Show. Not only does Warner herself emerge both politically and personally as a radical lesbian writer during this turbulent period of the 1930s. The article seeks to argue in this context that these three works also represent in themselves a progressively connected delineation of a lesbian continuum of women’s lives through the individual female and lesbian voices that are articulated in Warner’s writing at this crucial stage in her career.